Mode-Adaptive Surface Pattern Design for Enhanced Triboelectric Nanogenerator Performance - Masoumeh Karimi Kisomi; Muhammad Sohaib Roomi; M. A. Parvez Mahmud (Nanoenergy Advances)
Triboelectric nanogenerators (TENGs) are a promising technique for harvesting environmental energy that is based on electrostatic induction and contact electrification. This is a method that uses every relative motion between two electrodes to convert mechanical energy into electrical energy. Several modes of TENGs are designed based on various relative motions between electrode pairs. As TENGs are a surface phenomenon, properties such as the structure of the electrodes are key parameters that affect their performance. In this paper, in order to identify the best pattern designed adapted to the TENG mode, the effect of surface structures in each mode is investigated numerically. To achieve the best performance of the micro-patterned electrode, a comparative study has been conducted on the four TENG modes under the same conditions. To reach this goal, micro-patterned shapes such as pyramid, spherical, and cube structures are designed, and the open circuit voltage is calculated and compared to a flat surface. The results show that surface modification has a significant role in TENG’s performance. Based on this study, by using a cube-patterned electrode instead of a flat electrode, the output voltage increases from 233 V to 384 V in sliding mode. Also, by applying the spherical pattern, the output voltage is 1.7 times higher than a flat electrode in contact-separation mode. In the case of investigating TENG pattern structure, the results show that the electrical outputs of the patterned layer depend on the mode. The spherical pattern has a higher impact in contact-separation mode compared to the cube pattern. Meanwhile, in sliding mode, the cube pattern has a greater effect. This work provides a hint for designing an effective pattern on electrodes for a particular mode to enhance TENG performance.